The MAOA Gene Influences the Neural Response to Psychosocial Stress in the Human Brain - Sun, Xiaoqiang; Ming, Qingsen; Zhong, Xue; Dong, Daifeng; Li, Chuting; Xiong, Ge; Cheng, Chang; Cao, Wanyi; He, Jiayue; Wang, Xiang; Yi, Jinyao; Yao, Shuqiao (Frontiers in Behavioral Neuroscience, 2020)
The stress response is regulated by many mechanisms. Monoamine oxidase A (MAOA) has been related to many mental illnesses. However, few studies have explored the relationship between MAOA and acute laboratory-induced psychosocial stress with functional magnetic resonance imaging (fMRI). In the current study, the Montreal Imaging Stress Task (MIST) and fMRI were used to investigate how MAOA influences the stress response. Increased cortisol concentrations were observed after the task; functional connectivity between the bilateral anterior hippocampus and other brain regions was reduced during stress. MAOA-H allele carriers showed greater deactivation of the right anterior hippocampus and greater cortisol response after stress than did MAOH-L allele carriers. Hippocampal deactivation may lead to disinhibition of the hypothalamic-pituitary-adrenal (HPA) axis and the initiation of stress hormone release under stress. Our results suggest that the MAOA gene regulates the stress response by influencing the right anterior hippocampus.